A New Tool to Implement Gene Expression Data Analysis from the Allen Brain Atlas: A Practical Outcome of a Developmental Neuroscience Master's Class. (1st August 2021) - Rubino, Valerio; Bozzi, Yuri
Highlights: Academic teaching should exploit the potential of students' curiosity. We describe a teaching approach that succeeded in to generate meaningful results. We present a new, free algorithm to analyze gene expression data. Classes engaging students in data analysis my result in new research tools.